2008
DOI: 10.1016/j.rapm.2007.06.398
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Continuous Peripheral Nerve Block on the Inflammatory Response in Knee Arthroplasty

Abstract: Continuous lumbar plexus and sciatic nerve blocks with ropivacaine contribute to the attenuation of the postoperative inflammatory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 22 publications
2
30
0
1
Order By: Relevance
“…This stresses the importance of a local blockade of nerve transmission, to prevent the pain that would otherwise lead to local perineural inflammation phenomena, as compared to systemic treatment of inflammation and pain [20]. Thus, local analgesia appears to be better indicated to facilitate subsequent rehabilitation after total knee replacement [14], because by reducing pain, it allows patients to better tolerate early passive mobilization [17,21]. Some experimental works have shown that this form of analgesia, by inducing a blockade of C fibers through a mechanism that has not yet been entirely clarified, can inhibit perineural inflammation [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This stresses the importance of a local blockade of nerve transmission, to prevent the pain that would otherwise lead to local perineural inflammation phenomena, as compared to systemic treatment of inflammation and pain [20]. Thus, local analgesia appears to be better indicated to facilitate subsequent rehabilitation after total knee replacement [14], because by reducing pain, it allows patients to better tolerate early passive mobilization [17,21]. Some experimental works have shown that this form of analgesia, by inducing a blockade of C fibers through a mechanism that has not yet been entirely clarified, can inhibit perineural inflammation [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Various experiences have demonstrated that isolated blockade of the femoral nerve can achieve a better postoperative analgesia than blockade of the sciatic nerve or combined sciatic and femoral blockade. This suggests that the posterior territory, innervated by the sciatic nerve, may contribute only marginally to the onset of postoperative pain [21].…”
Section: Discussionmentioning
confidence: 99%
“…These leukocytes gather at the site of inflammation, causing the release of cytokines, resulting in a more robust local immune responss. 36 Surgical trauma has been shown to provoke an inflammatory state that causes the release of inflammatory cytokines. This cytokine release results in inflammation at the sight of injury as well as inflammation that cause systemic effects.…”
Section: Inflammatory Responsementioning
confidence: 99%
“…Similarly, synthesis of acute phase proteins produced in the liver also play a role in the stress response, as well as the modulation and release of inflammatory cytokines. 36 Reducing the inflammatory response can lead to decreased immunosuppression which enhances recovery. 36,44 Release of substance P and neurokinin have been shown in murine models to induce peripheral inflammation.…”
Section: Inflammatory Responsementioning
confidence: 99%
See 1 more Smart Citation